Advancing nutrition: Food system policies and actions for healthy diets - Menon, Purnima; Olney, Deanna K. (International Food Policy Research Institute, 2024)
Hunger, food insecurity, and unhealthy diets underpin many critical public health challenges, including all forms of malnutrition and diet-related noncommunicable diseases. These health outcomes, in turn, have short- and long-term impacts on the well-being and productivity of human populations worldwide. Amid these complex, interconnected challenges, the global focus on how to leverage food systems for nutrition has shifted toward sustainable healthy diets that promote well-being for both people and the planet. This chapter provides an overview of the thematic chapters of the 2024 Global Food Policy Report, which look at food demand and affordability, food environments, plant- and animal-source foods, and governance for sustainable healthy diets.